2016
DOI: 10.1007/s00267-016-0668-4
|View full text |Cite
|
Sign up to set email alerts
|

Can Artificial Ecosystems Enhance Local Biodiversity? The Case of a Constructed Wetland in a Mediterranean Urban Context

Abstract: Constructed wetlands (CW) are considered a successful tool to treat wastewater in many countries: their success is mainly assessed observing the rate of pollution reduction, but CW can also contribute to the conservation of ecosystem services. Among the many ecosystem services provided, the biodiversity of CW has received less attention. The EcoSistema Filtro (ESF) of the Molentargius-Saline Regional Natural Park is a constructed wetland situated in Sardinia (Italy), built to filter treated wastewater, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…[56] Constructed wetlands with emergent vegetation show a greater potential for maintaining vegetation diversity and increase the likelihood of colonization by a more diverse assemblage of macroinvertebrates [54]. One CW in the Regional Natural Park, Italy, was found to maintain a vegetation community consisting of 54% of the floral species pool of the whole park, despite covering just 2.52% of the total park area [55]. The development of a diverse vegetation community is also attributed to the presence of visiting and nesting birds [20].…”
Section: Effluent Water From a Sewage Treatment Plantmentioning
confidence: 99%
“…[56] Constructed wetlands with emergent vegetation show a greater potential for maintaining vegetation diversity and increase the likelihood of colonization by a more diverse assemblage of macroinvertebrates [54]. One CW in the Regional Natural Park, Italy, was found to maintain a vegetation community consisting of 54% of the floral species pool of the whole park, despite covering just 2.52% of the total park area [55]. The development of a diverse vegetation community is also attributed to the presence of visiting and nesting birds [20].…”
Section: Effluent Water From a Sewage Treatment Plantmentioning
confidence: 99%
“…Accordingly, a proper drainage system such as SUDS [28], [29] should be considered for roadside verges and central reserves if engineered to capture carbon in addition to their primary functions. A further benefit of SUDS is that the created wetland can provide habitat for supporting biodiversity [30], [31].…”
Section: Discussionmentioning
confidence: 99%
“…Their success has mainly been assessed in terms of water purification performance. Moreover, constructed wetlands can contribute to maintaining or improving biodiversity, especially in urban areas [120]. However, this aspect has received little attention so far.…”
Section: Impacts Of Constructed Wetlands On Biodiversitymentioning
confidence: 99%
“…A focus of constructed wetland research is the influence of plants on microorganisms and, specifically, on their performance in the decomposition of substances contained in water [163][164][165][166][167]. In the arrival and establishment phase of wetland succession, the plant diversity of constructed wetlands can exceed that of established natural wetlands [120,168,169]. A comprehensive study of vascular plants in a constructed wetland in Grady County, Georgia in the United States showed that their diversity had increased by a factor of 24 over a 9-year period since it was set up.…”
Section: Opportunities To Increase Biodiversity In Constructed Wetlandsmentioning
confidence: 99%